Workplace Connections and Labor Migration: The Role of Information in Shaping Expectations - Michelle Hansch; Jan Nimczik; Alexandra Spitz-Oener (Ludwig-Maximilians-Universität München und Humboldt-Universität zu Berlin, Collaborative Research Center Transregio 190 - Rationality and Competition, 2024)
In a context where improved employment outcomes entail relocating to a new destination, how does information from former coworkers alter workers' labor migration decisions? We explore this question using the unique backdrop of German reunification in the early 1990s. For former workers of the German Democratic Republic (GDR), improving employment outcomes typically meant relocating to West Germany, which most were reluctant to do. We show that information from former GDR coworkers in West Germany significantly increased the employment probability of East Germans in West Germany. To identify these network effects, we document and exploit that GDR workers were as-good-as randomly assigned to networks by the GDR system from the perspective of the West German market economy. We then establish that the networks only trigger migration responses among East Germans whose contacts had positive work experiences in the West and were similar in their earnings potential in the market-based economy of reunified Germany. These contacts, in essence, serve as role models for the workers' prospects in the West, leading workers to trust the advice and assessments provided and ultimately altering the expected benefits from labor migration for the specific worker.
Keywords: 330